Pebbles -- using Circular Treemaps to visualize disk usage - Wetzel, Kai (2003)
During the 1990s Ben Shneiderman of the Human-Computer Interaction Laboritory (HCIL) of the University of Maryland invented Treemaps as a "compact visualization of directory tree structures". Treemaps involve "turning a tree into a planar space-filling" representation. Unlike other variations such as squarified treemaps, or cushion treemaps, circular treemaps as presented here could be considered an evolutionary dead-end (rejected early by Ben Shneiderman) but at least I think it's a pretty one.